Roaring Days: Rossland's Mines and the History of British Columbia - Mouat, Jeremy (UBC Press, 1995)
In the 1890s, Rossland was the most important mining centre in southeastern British Columbia. In Roaring Days, Jeremy Mouat examines many different aspects of mining, from work underground to corporate strategies. He also brings to life the unique individuals who were a part of this history – the miners who toiled long hours under unimaginable working conditions, the citizens of Rossland who built a bustling town out of the wilderness, and the mine owners and entrepreneurs who became wealthy beyond all expectations. –Publisher's description
https://www.ubcpress.ca/roaring-days